Silicon-carbon composite material, preparation method thereof and lithium ion battery containing silicon-carbon composite material
Through the use of silicon-carbon composite materials, the problems of poor conductivity and volume expansion of silicon-based anode materials in lithium-ion batteries are solved, and high energy density and high cycle stability are achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202411520768.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2024-12-31
AI Technical Summary
The existing silicon-based anode materials in lithium-ion batteries have attenuated battery performance due to poor conductivity and volume expansion, which cannot meet the needs of high energy density and high-speed current charging.
Silicon-carbon composite materials are used to combine biomass carbon-based silicon-carbon materials with resin carbon-based silicon-carbon materials and prepared by low-temperature coating to form high compaction, high fast charging performance and high cycle stability. silicon-carbon composite material.
It improves the energy density and dynamic performance of lithium-ion batteries, extends the cycle life of the battery, reduces process costs, and is suitable for industrial mass production.
Smart Images

Figure CN119230793A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a silicon-carbon composite material, a preparation method thereof and a lithium-ion battery comprising the same. Background Art
[0002] Graphite has become the most commonly used commercial negative electrode material for lithium-ion batteries due to its low cost, high chemical stability and good processing performance. However, with the development of electric vehicles and energy storage, the theoretical capacity of existing graphite materials has reached its limit and the small theoretical interlayer spacing of graphite cannot meet the needs of high energy density and high-rate current charging. A large rate will cause surface lithium deposition and destruction of the graphite structure, resulting in a decrease in battery capacity and cycle performance. Silicon materials are expected to become one of the negative electrode materials for high-energy lithium-ion batteries that can replace graphite because of their extremely high theoretical specific capacity (up to 4200mAh / g) and abundant resources. However, silicon materials will undergo huge volume changes during the process of lithium insertion / extraction, resulting in the pulverization and shedding of active materials, which in turn leads to a sharp decrease in the capacity of silicon-based negative electrode batteries.
[0003] The commonly used simple optimization scheme is to combine silicon material with a certain proportion of graphite material to obtain silicon@graphite composite negative electrode material. Unfortunately, although this method greatly improves the energy density of silicon material, the battery performance degradation problem caused by the poor conductivity of silicon material and huge volume expansion is still serious.
[0004] CN107565117A provides a method for preparing a silicon / graphite composite negative electrode material, wherein nano silicon and graphite are mixed in a specific ratio and supplemented with an auxiliary agent, and the negative electrode material is prepared by ball milling, thereby improving the electronic conductivity of the electrode; at the same time, the binder is evenly dispersed on the surface of the silicon particles during the ball milling process, forming an effective covering and protection, reducing the oxidation of the nano silicon, playing a role in stabilizing the silicon particles, and improving the cycle life and rate performance of the battery, but the improvement effect is limited, and more in-depth research is still needed to further improve the comprehensive performance of silicon-based negative electrode batteries. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a silicon-carbon composite material, a preparation method thereof and a lithium-ion battery comprising the same.
[0006] In a first aspect, the present invention provides a silicon-carbon composite material, the silicon-carbon composite material comprising a mixed silicon-carbon material and a carbon coating layer coated on the surface of the mixed silicon-carbon material;
[0007] The mixed silicon-carbon material includes a biomass-based carbon-based silicon-carbon material and a resin-based carbon-based silicon-carbon material;
[0008] In the silicon-carbon composite material, by mass percentage, the content of the biomass carbon-based silicon-carbon material is 25-45wt%, the content of the resin carbon-based silicon-carbon material is 50-70wt%, and the content of the carbon coating layer does not exceed 5wt%.
[0009] In some embodiments of the present invention, the D50 particle size of the biomass-based carbon-based silicon-carbon material is 0.5-5 μm, preferably 1-3 μm.
[0010] In some embodiments of the present invention, the pore size of the biomass-based carbon-based silicon-carbon material is 0.3-500 nm.
[0011] In some embodiments of the present invention, in the biomass-based carbon-based silicon-carbon material, the carbon content is 50-70wt%, and the silicon content is 30-50wt%, by mass percentage.
[0012] In some embodiments of the present invention, the D50 particle size of the resin-based carbon-based silicon-carbon material is 3-8 μm, preferably 3-5 μm.
[0013] In some embodiments of the present invention, the pore size of the mesopores is 5-20 nm, and the pore size of the micropores is 0.1-2 nm.
[0014] In some embodiments of the present invention, in the resin-based carbon-based silicon-carbon material, the carbon content is 50-70wt%, and the silicon content is 30-50wt%, by mass percentage.
[0015] In some embodiments of the present invention, the aspect ratio γ of each particle of the resin-based carbon-based silicon-carbon material satisfies 0.6≤γ≤1, preferably 0.7≤γ<1.
[0016] In some embodiments of the present invention, the D50 particle size of the silicon-carbon composite material is 10-25 μm, preferably 12-20 μm.
[0017] In some embodiments of the present invention, in each silicon-carbon composite material particle, the number of particles of the biomass-based carbon-based silicon-carbon material is 1-3 on average.
[0018] In some embodiments of the present invention, in each silicon-carbon composite material particle, the number of particles of the resinous carbon-based silicon-carbon material is 2-4 on average.
[0019] In some embodiments of the present invention, the thickness d of the carbon coating layer satisfies 100 nm. <d<200nm。
[0020] In a second aspect, the present invention provides a method for preparing the silicon-carbon composite material as described in the first aspect, the preparation method comprising the following steps:
[0021] (1) first mixing a biomass-based carbon-based silicon-carbon material and a resin-based carbon-based silicon-carbon material to obtain a mixed dry material;
[0022] (2) performing a second mixing of the mixed dry material obtained in step (1) and the coating agent, and then granulating and coating the mixed dry material to obtain a silicon-carbon composite material precursor;
[0023] (3) Carbonizing the silicon-carbon composite material precursor obtained in step (2) to obtain a silicon-carbon composite material.
[0024] In some embodiments of the present invention, the time of the first mixing in step (1) is 10-30 min, preferably 15-25 min.
[0025] In some embodiments of the present invention, the time of the second mixing in step (2) is 20-60 min, preferably 25-40 min.
[0026] In some embodiments of the present invention, the coating agent in step (2) includes a solid-phase coating agent or a liquid-phase coating agent.
[0027] In some embodiments of the present invention, the solid phase coating agent includes one or more of asphalt, coal tar or petroleum tar, preferably coal tar and / or petroleum tar.
[0028] In some embodiments of the present invention, the liquid coating agent is a resin solution.
[0029] In some embodiments of the present invention, the resin in the resin solution includes phenolic resin and / or epoxy resin.
[0030] In some embodiments of the present invention, the solvent in the resin solution includes one or more of a ketone solvent, an alcohol solvent, a halogenated alkane solvent or an ether solvent.
[0031] In some embodiments of the present invention, the temperature of the carbonization treatment in step (3) is 300-800°C, preferably 400-600°C.
[0032] In some embodiments of the present invention, the heating rate of the carbonization treatment in step (3) is 2-10°C / min, preferably 5-8°C / min.
[0033] In some embodiments of the present invention, the holding time of the carbonization treatment in step (3) is 100-200 minutes.
[0034] In some embodiments of the present invention, the carbonization treatment in step (3) is performed under a protective atmosphere.
[0035] In a third aspect, the present invention provides a negative electrode plate for a lithium-ion battery, comprising the silicon-carbon composite material as described in the first aspect, or the silicon-carbon composite material prepared by the preparation method as described in the second aspect.
[0036] In a fourth aspect, the present invention provides a method for preparing a negative electrode sheet of a lithium ion battery, comprising:
[0037] (1) mixing a negative electrode active material, a conductive agent, a binder and a solvent to obtain a negative electrode slurry;
[0038] The negative electrode active material includes the silicon-carbon composite material and a graphite material;
[0039] In the negative electrode active material, the mass ratio of the silicon-carbon composite material to the graphite material is 1:(3.5-4.5);
[0040] (2) The negative electrode slurry obtained in step (1) is coated on the front and back surfaces of the negative electrode current collector to form a coating layer, which is then dried, rolled and cut in sequence to obtain a negative electrode sheet for a lithium-ion battery.
[0041] In some embodiments of the present invention, step (1) specifically comprises: first mixing the silicon-carbon composite material, the graphite material and a portion of the conductive agent to obtain a premixed dry material;
[0042] performing a second mixing of the binder and a portion of the solvent to obtain a binder solution;
[0043] The premixed dry material, the remaining conductive agent, part of the binder solution and the remaining solvent are mixed for the third time to obtain a first mixed solution; the first mixed solution and the remaining binder solution are mixed for the fourth time to obtain a negative electrode slurry.
[0044] In some embodiments of the present invention, the conductive agent includes but is not limited to one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotube or graphene.
[0045] In some embodiments of the present invention, the binder comprises carboxymethyl cellulose (CMC) and / or polyacrylic acid (PAA).
[0046] In some embodiments of the present invention, the solvent comprises water.
[0047] In some embodiments of the present invention, in the negative electrode slurry, the mass proportion of the negative electrode active material is 90-96wt%, the mass proportion of the conductive agent is 1.5-5wt%, and the mass proportion of the binder is 2.5-5wt%; the solid content of the negative electrode slurry is 40-50%.
[0048] In a fifth aspect, the present invention provides a lithium-ion battery, comprising the lithium-ion battery negative electrode sheet as described in the third aspect.
[0049] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:
[0050] (1) The present invention compounds two different carbon-based silicon-carbon materials, uses a resin-based silicon-carbon material with high sphericity as a support, and uses a biomass-based silicon-carbon material to improve the fast charging performance of the composite material, thereby constructing a silicon-carbon composite material that takes into account high compaction, high fast charging performance and high cycle stability, which is beneficial to the application and development of silicon-based negative electrode batteries.
[0051] (2) The present invention prepares the silicon-carbon composite material by a low-temperature coating method, which has simple process operation and low cost, and is conducive to industrial mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] Figure 1 A schematic structural diagram of the silicon-carbon composite material provided for a specific embodiment of the present invention.
[0053] Among them, 1-biomass carbon-based silicon-carbon material; 2-resin carbon-based silicon-carbon material; 3-carbon coating layer. DETAILED DESCRIPTION
[0054] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.
[0055] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.
[0056] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0057] In a first aspect, the present invention provides a silicon-carbon composite material, the silicon-carbon composite material comprising a mixed silicon-carbon material and a carbon coating layer coated on the surface of the mixed silicon-carbon material;
[0058] The mixed silicon-carbon material includes a biomass-based carbon-based silicon-carbon material and a resin-based carbon-based silicon-carbon material;
[0059] In the silicon-carbon composite material, the content of the biomass carbon-based silicon-carbon material is 25-45wt%, such as 25wt%, 30wt%, 35wt%, 40wt% and 45wt% by mass; the content of the resin carbon-based silicon-carbon material is 50-70wt%, such as 50wt%, 55wt%, 60wt%, 65wt% and 70wt%; the content of the carbon coating layer does not exceed 5wt%, such as 1wt%, 2wt%, 3wt%, 4wt% and 5wt%, but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0060] The morphology of biomass carbon-based silicon-carbon materials is not specifically limited. The material has a large pore structure and more active sites, which are beneficial to the transmission of electrolytes and the diffusion of lithium ions, and has good rate performance. However, the material has a small compaction and is easily broken after rolling, which leads to the occurrence of side reactions, increased silicon-carbon volume expansion, and decreased cycle stability; resin-based carbon silicon-carbon materials have high morphology controllability, high compaction density, and more mesopores and micropores, which can effectively isolate the electrolyte from the silicon crystal reaction, and have good cycle stability, but their fast charging performance is average. The present invention compounds the above two silicon-carbon materials (both primary particles), uses a resin-based silicon-carbon material with high sphericity as a support, and uses a biomass-based silicon-carbon material to improve the fast charging performance of the composite material, thereby obtaining a silicon-carbon composite material (secondary particles) with high compaction, high fast charging performance and high cycle stability, and promoting the development of silicon-based negative electrode batteries.
[0061] In addition, a reasonable material ratio helps to further improve the comprehensive performance of the silicon-carbon composite material. If there is too much biomass-based carbon-based silicon-carbon material, the compaction density of the silicon-carbon composite material will be small, and it will be easy to break after rolling, which will lead to the occurrence of side reactions, increased silicon-carbon volume expansion, and decreased cycle stability; if there is too much resin-based carbon-based silicon-carbon material, although it can increase the cycle stability of the obtained composite material, it will cause its fast charging performance to decrease.
[0062] In some embodiments of the present invention, in the biomass-based carbon-based silicon-carbon material, the choice of biomass-based carbon-based precursor is not specifically limited. For example, it can be one or more of coconut shells, peanut shells, egg shells, bamboo, banana leaves or reeds, such as a combination of coconut shells, bamboo and reeds, a combination of peanut shells and egg shells, etc., preferably one or more of coconut shells, bamboo, reeds or banana leaves.
[0063] In some embodiments of the present invention, in the resin-based carbon-based silicon-carbon material, the choice of the resin-based carbon-based precursor is not specifically limited. For example, it can be one or more of phenolic resin, furan resin, epoxy resin, furfural resin, furfural ketone resin or furfuryl alcohol resin, such as a combination of phenolic resin and furan resin, a combination of furan resin, epoxy resin and furfural resin, etc., preferably one or more of phenolic resin, furan resin, epoxy resin or furfural resin.
[0064] In some embodiments of the present invention, the preparation methods of the biomass-based carbon-based silicon-carbon material and the resin-based carbon-based silicon-carbon material are not specifically limited and can be selected from the prior art according to actual needs, for example, such as CVD vapor deposition method.
[0065] The process of preparing biomass carbon-based silicon-carbon material or resin carbon-based silicon-carbon material by CVD vapor deposition method includes:
[0066] S1: crushing the biomass porous carbon or the resin porous carbon;
[0067] S2: heating the crushed biomass porous carbon or resin porous carbon in a protective atmosphere, then introducing a silicon source gas to perform silicon deposition, and controlling the temperature to be 600-800° C. to obtain a first precursor;
[0068] S3: placing the first precursor in a carbon source gas for pyrolysis at a pyrolysis temperature of 600-800° C. to obtain a biomass-based carbon-based silicon-carbon material or a resin-based carbon-based silicon-carbon material.
[0069] The choice of silicon source gas is not specifically limited. For example, it can be one or more of monosilane, disilane, dichlorosilane or trichlorosilane, such as a combination of monosilane and disilane, a combination of dichlorosilane and trichlorosilane, etc.
[0070] The choice of carbon source gas is not particularly limited. For example, it can be one or more of methane, acetylene, ethylene or propylene, such as a combination of methane and acetylene, a combination of ethylene and propylene, and the like.
[0071] In some embodiments of the present invention, the D50 particle size of the biomass-based carbon-based silicon-carbon material is 0.5-5 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, etc., but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 1-3 μm.
[0072] In some embodiments of the present invention, the D50 particle size of the resin-based carbon-based silicon-carbon material is 3-8 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, but is not limited to the listed values. Other unlisted values within the range are also applicable, preferably 3-5 μm.
[0073] In some embodiments of the present invention, the D50 particle size of the silicon-carbon composite material is 10-25 μm, for example, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm or 25 μm, but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 12-20 μm.
[0074] In the present invention, regarding the biomass carbon-based silicon-carbon material, the resin carbon-based silicon-carbon material and the silicon-carbon composite material, the appropriate particle size ratio helps to improve the initial efficiency and high-temperature performance of the lithium-ion battery, control the reasonable ion transmission path length, and at the same time, in the process of preparing the negative electrode sheet of the lithium-ion battery, it can be evenly dispersed among the graphite particles, thereby improving the rate performance and avoiding lithium precipitation.
[0075] It should be noted that the median particle size D50 in the present invention refers to the volume median particle size.
[0076] Exemplarily, the volume median particle size D50 of each material in the present invention is obtained using a laser diffraction particle size analyzer (MS2000). The determination method includes: dispersing the sample particles in a liquid medium at a concentration of 200-300 mg / L, and allowing a monochromatic light beam to pass therethrough. After the light is scattered by the particles, it is distributed at different angles, and the regular multi-element detector receives the values of the relevant scattering diagram at many angles, and records these values for analysis. Then, the Rayleigh scattering formula is used to calculate the scattering values to obtain the ratio of the volume of particles of each particle size level to the total volume, thereby obtaining the volume distribution of the particle size.
[0077] In some embodiments of the present invention, the pore size of the biomass-based carbon-based silicon-carbon material is 0.3-500nm, for example, 0.3nm, 5nm, 10nm, 100nm, 200nm, 400nm or 500nm, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0078] In some embodiments of the present invention, in the biomass carbon-based silicon-carbon material, the carbon content, by mass percentage, is 50-70wt%, for example, 50wt%, 55wt%, 60wt%, 65wt% or 70wt%, etc.; the silicon content is 30-50wt%, for example, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, etc., but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0079] In some embodiments of the present invention, the resin-based carbon-based silicon-carbon material has mesopores and micropores; the pore size of the mesopores is 5-20nm, for example, 5nm, 10nm, 15nm or 20nm, etc.; the pore size of the micropores is 0.1-2nm, for example, 0.1nm, 0.5nm, 1nm, 1.5nm or 2nm, etc., and other unlisted values within the above range are also applicable.
[0080] In some embodiments of the present invention, in the resin-based carbon-based silicon-carbon material, the carbon content, by mass percentage, is 50-70wt%, for example, 50wt%, 55wt%, 60wt%, 65wt% or 70wt%, etc.; the silicon content is 30-50wt%, for example, 30wt%, 35wt%, 40wt%, 45wt% or 50wt%, etc., but is not limited to the listed values, and other values not listed within the above range are also applicable.
[0081] In some embodiments of the present invention, the aspect ratio γ of each particle of the resin-based carbon-based silicon-carbon material satisfies 0.6≤γ≤1, and γ can be 0.6, 0.7, 0.8, 0.9 or 1, etc., but is not limited to the listed values. Other unlisted values within the range are also applicable, preferably 0.7≤γ<1.
[0082] In the present invention, the resin-based carbon-based silicon-carbon material particles have a higher compaction density as the sphericity increases. As a compressive component, the resin-based carbon-based silicon-carbon material particles greatly avoid the silicon-carbon composite material from being crushed after rolling, exposing the silicon material to the electrolyte, thereby increasing the occurrence of more side reactions. Moreover, as the sphericity increases, it is more conducive to improving the high-temperature performance of the battery.
[0083] In some embodiments of the present invention, in each silicon-carbon composite material particle, the number of particles of the biomass-based carbon-based silicon-carbon material is 1-3 on average, for example, 1, 2 or 3.
[0084] In some embodiments of the present invention, in each silicon-carbon composite material particle, the number of particles of the resinous carbon-based silicon-carbon material is 2-4 on average, for example, 2, 3 or 4.
[0085] In the present invention, the appropriate ratio of the number of biomass carbon-based silicon-carbon material particles to the number of resin carbon-based silicon-carbon material particles helps to improve the performance of the silicon-carbon composite material. If the number of the two materials in the carbon coating layer is small, the particle size of the resulting silicon-carbon composite material will be small, thereby reducing its compaction ability, and will also lead to more side reactions in the lithium-ion battery and deterioration of high-temperature cycle performance; while if the number of the two materials in the carbon coating layer is large, the particle size of the resulting silicon-carbon composite material will be large, the ion transmission path will increase, and the fast charging performance will be deteriorated.
[0086] In some embodiments of the present invention, the thickness d of the carbon coating layer satisfies 100 nm < d < 200 nm, such as 110 nm, 130 nm, 150 nm, 180 nm, or 199 nm, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable.
[0087] Second, the present invention provides a method for preparing the silicon-carbon composite material as described in the first aspect, and the preparation method includes the following steps:
[0088] (1) First mix the biomass-based carbonaceous silicon-carbon material and the resin-based carbonaceous silicon-carbon material to obtain a mixed dry material;
[0089] (2) Second mix the mixed dry material obtained in step (1) with a coating agent, and then perform granulation coating to obtain a silicon-carbon composite precursor;
[0090] (3) Carbonize the silicon-carbon composite precursor obtained in step (2) to obtain a silicon-carbon composite material.
[0091] The preparation method of the present invention has simple process operation and low cost, which is beneficial to industrial mass production.
[0092] In some embodiments of the present invention, the time of the first mixing in step (1) is 10 - 30 min, such as 10 min, 15 min, 20 min, 25 min, or 30 min, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable, and preferably 15 - 25 min.
[0093] In some embodiments of the present invention, the time of the second mixing in step (2) is 20 - 60 min, such as 20 min, 30 min, 40 min, 50 min, or 60 min, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable, and preferably 25 - 40 min.
[0094] In some embodiments of the present invention, the equipment selected for granulation coating in step (2) includes but is not limited to any one of a rotary drum carbon coating equipment, a fluidized bed spraying carbon coating equipment, a spray dryer, or a particle granulator.
[0095] In some embodiments of the present invention, the coating agent in step (2) includes a solid-phase coating agent or a liquid-phase coating agent.
[0096] In some embodiments of the present invention, the solid-phase coating agent includes one or more of pitch, coal tar, or petroleum tar, and preferably coal tar and / or petroleum tar.
[0097] In some embodiments of the present invention, the liquid coating agent is a resin solution.
[0098] In some embodiments of the present invention, the resin in the resin solution includes phenolic resin and / or epoxy resin.
[0099] In some embodiments of the present invention, the solvent in the resin solution includes one or more of ketone solvents, alcohol solvents, halogenated alkane solvents, ether solvents or ester solvents, such as a combination of alcohol solvents and ether solvents, a combination of ketone solvents and halogenated alkane solvents, etc.
[0100] In some embodiments of the present invention, the alcohol solvent includes, but is not limited to, one or more of ethanol, propanol or butanol.
[0101] In some embodiments of the present invention, the halogenated alkane solvent includes but is not limited to chloroform and / or dichloromethane.
[0102] In some embodiments of the present invention, the ketone solvent includes but is not limited to acetone and / or methyl ethyl ketone.
[0103] In some embodiments of the present invention, the ether solvent includes, but is not limited to, one or more of diethyl ether, isopropyl ether, methyl ether or dimethyl ether.
[0104] In some embodiments of the present invention, the ester solvent includes but is not limited to methyl formate and / or methyl acetate.
[0105] In some embodiments of the present invention, the temperature of the carbonization treatment in step (3) is 300-800°C, for example, 300°C, 400°C, 500°C, 600°C, 700°C or 800°C, but is not limited to the listed values. Other unlisted values within the range are also applicable, preferably 400-600°C.
[0106] The preparation method of the present invention adopts a low-temperature coating method, the coating is more uniform, the energy consumption is low, and it is conducive to industrial production.
[0107] In some embodiments of the present invention, the heating rate of the carbonization treatment in step (3) is 2-10°C / min, for example, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values within the range are also applicable, preferably 5-8°C / min.
[0108] In some embodiments of the present invention, the holding time of the carbonization treatment in step (3) is 100-200 min, for example, 100 min, 120 min, 140 min, 160 min, 180 min or 200 min, but is not limited to the listed values, and other unlisted values within the range are also applicable.
[0109] In some embodiments of the present invention, the carbonization treatment in step (3) is performed under a protective atmosphere.
[0110] In some embodiments of the present invention, the protective atmosphere includes any one of an argon atmosphere, a helium atmosphere or a neon atmosphere.
[0111] In a third aspect, the present invention provides a negative electrode plate for a lithium-ion battery, comprising the silicon-carbon composite material as described in the first aspect, or the silicon-carbon composite material prepared by the preparation method as described in the second aspect.
[0112] In a fourth aspect, the present invention provides a method for preparing a negative electrode sheet of a lithium ion battery, comprising:
[0113] (1) mixing a negative electrode active material, a conductive agent, a binder and a solvent to obtain a negative electrode slurry;
[0114] The negative electrode active material includes the silicon-carbon composite material and a graphite material;
[0115] In the negative electrode active material, the mass ratio of the silicon-carbon composite material to the graphite material is 1:(3.5-4.5);
[0116] The above mass ratio can be 1:3.5, 1:3.7, 1:4, 1:4.2 or 1:4.5, etc., but is not limited to the listed values, and other values not listed within the range are also applicable;
[0117] (2) The negative electrode slurry obtained in step (1) is coated on the front and back surfaces of the negative electrode current collector to form a coating layer, which is then dried, rolled and cut in sequence to obtain a negative electrode sheet for a lithium-ion battery.
[0118] In some embodiments of the present invention, step (1) specifically comprises: first mixing the silicon-carbon composite material, the graphite material and a portion of the conductive agent to obtain a premixed dry material;
[0119] performing a second mixing of the binder and a portion of the solvent to obtain a binder solution;
[0120] The premixed dry material, the remaining conductive agent, part of the binder solution and the remaining solvent are mixed for the third time to obtain a first mixed solution; the first mixed solution and the remaining binder solution are mixed for the fourth time to obtain a negative electrode slurry.
[0121] In some embodiments of the present invention, the conductive agent includes but is not limited to one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotubes and graphene.
[0122] In some embodiments of the present invention, the binder comprises carboxymethyl cellulose (CMC) and / or polyacrylic acid (PAA).
[0123] In some embodiments of the present invention, the solvent comprises water.
[0124] In some embodiments of the present invention, in the negative electrode slurry, the mass proportion of the negative electrode active material is 90-96wt%, such as 90wt%, 92wt%, 94wt% or 96wt%, etc.; the mass proportion of the conductive agent is 1.5-5wt%, such as 1.5wt%, 2wt%, 3wt%, 4wt% or 5wt%, etc.; the mass proportion of the binder is 2.5-5wt%, such as 2.5wt%, 3wt%, 4wt% or 5wt%, etc.; the solid content of the negative electrode slurry is 40-50%, such as 40%, 42%, 45%, 48% or 50%, etc., but is not limited to the listed values, and other unlisted values within their respective ranges are equally applicable.
[0125] In a fifth aspect, the present invention provides a lithium-ion battery, comprising the lithium-ion battery negative electrode sheet as described in the third aspect.
[0126] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention clearer, the present invention will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its applications. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0127] If no specific techniques or conditions are specified in the examples, the conventional techniques or conditions in the art, or the techniques or conditions described in the literature, or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0128] For example, in the following examples and comparative examples, the biomass-based carbon-based silicon-carbon material and the resin-based carbon-based silicon-carbon material are prepared by CVD vapor deposition method.
[0129] The method for preparing a biomass-based carbon-based silicon-carbon material or a resin-based carbon-based silicon-carbon material by using a CVD vapor deposition method comprises:
[0130] S1: crushing the biomass porous carbon or the resin porous carbon;
[0131] S2: heating the crushed biomass porous carbon or resin porous carbon in a protective atmosphere, then introducing a silicon source gas to perform silicon deposition, and controlling the temperature to be 600-800° C. to obtain a first precursor;
[0132] S3: placing the first precursor in a carbon source gas for pyrolysis at a pyrolysis temperature of 600-800° C. to obtain a biomass-based carbon-based silicon-carbon material or a resin-based carbon-based silicon-carbon material.
[0133] It should be noted that based on the above-mentioned CVD vapor deposition method, the D50 particle size of the silicon-carbon material is controlled by regulating the particle size of the carbon matrix, and the silicon and carbon content are controlled by regulating the silicon source gas concentration, deposition time and deposition temperature. Those skilled in the art can adjust the preparation conditions according to the final product data to obtain the desired biomass carbon-based silicon-carbon material and resin carbon-based silicon-carbon material.
[0134] It should be noted that the preparation of the biomass-based carbon-based silicon-carbon material and the resin-based carbon-based silicon-carbon material in the present invention is not limited to this one preparation method, and other methods in the prior art that can prepare the above two materials can be used.
[0135] The present invention provides a silicon-carbon composite material and a preparation method thereof. The structural schematic diagram of the silicon-carbon composite material is as follows: Figure 1 The silicon-carbon composite material comprises a mixed silicon-carbon material, and the mixed silicon-carbon material comprises a biomass carbon-based silicon-carbon material 1 and a resin carbon-based silicon-carbon material 2;
[0136] The silicon-carbon composite material further includes a carbon coating layer 3 coated on the surface of the mixed silicon-carbon material;
[0137] In the silicon-carbon composite material, by mass percentage, the content of the biomass carbon-based silicon-carbon material 1 is 25-45wt%, the content of the resin carbon-based silicon-carbon material 2 is 50-70wt%, and the content of the carbon coating layer 3 is 0-5wt%.
[0138] The D50 particle size of the biomass carbon-based silicon-carbon material 1 is denoted as D1, which satisfies 0.5≤D1≤5μm, and the pore size is 0.3-500nm, wherein the carbon content is 50-70wt%, and the silicon content is 30-50wt%.
[0139] The resin-based carbon-based silicon-carbon material 2 has mesopores and micropores, and its D50 particle size is denoted as D2, satisfying 3≤D2≤8μm, wherein the pore size of the mesopores is 5-20nm, the pore size of the micropores is 0.1-2nm, the carbon content is 50-70wt%, the silicon content is 30-50wt%, and the aspect ratio γ of each particle of the resin-based silicon-carbon material 2 satisfies 0.6≤γ≤1.
[0140] The D50 particle size of the silicon-carbon composite material is denoted as D3, satisfying 10≤D3≤25 μm.
[0141] In each silicon-carbon composite material particle, the average number of particles of the biomass carbon-based silicon-carbon material 1 is recorded as A1, satisfying 1≤A1≤3, and the average number of particles of the resin carbon-based silicon-carbon material 2 is recorded as A2, satisfying 2≤A2≤4.
[0142] The thickness of the carbon coating layer 3 is denoted as d, which satisfies 100 nm. <d<200nm。
[0143] Wherein, the volume median particle size D50 of each material in the present invention is obtained using a laser diffraction particle size analyzer (MS2000). The determination method includes: dispersing the sample particles in a liquid medium at a concentration of 200-300 mg / L, and allowing a monochromatic light beam to pass therethrough. After the light is scattered by the particles, it is distributed at different angles, and the values of the relevant scattering diagrams received by the regular multi-element detector at many angles are recorded for analysis. Then, the Rayleigh scattering formula is used to calculate the scattering values, and the ratio of the volume of particles of each particle size level to the total volume is obtained, thereby obtaining the volume distribution of the particle size.
[0144] The preparation method comprises the following steps:
[0145] (1) a biomass-based carbon-based silicon-carbon material 1 and a resin-based carbon-based silicon-carbon material 2 are first mixed for a mixing time of 10-30 min to obtain a mixed dry material;
[0146] (2) performing a second mixing of the mixed dry material obtained in step (1) and the coating agent for a mixing time of 20-60 min, and then granulating and coating to obtain a silicon-carbon composite material precursor;
[0147] (3) Under a protective atmosphere, the silicon-carbon composite material precursor obtained in step (2) is carbonized at 300-800° C., the heating rate is controlled to be 2-10° C. / min, and the holding time is 100-200 min to obtain a silicon-carbon composite material.
[0148] Examples 1-14 and Comparative Examples 1-9 respectively provide a silicon-carbon composite material and a preparation method.
[0149] The silicon-carbon composite material refers to the silicon-carbon composite material in the specific embodiment, and the condition parameters of the obtained silicon-carbon composite material are shown in Table 1. Among them, in the biomass carbon-based silicon-carbon material 1, the carbon content is 55wt%, the silicon content is 45wt%, and the pore size range is 0.3-500nm; in the resin carbon-based silicon-carbon material 2, the carbon content is 55wt%, the silicon content is 45wt%, the mesopore pore size range is 5-20nm, and the micropore pore size range is 0.1-2nm.
[0150] The preparation method is described in detail in the specific embodiment, and the specific conditions and parameters are shown in Table 2.
[0151] Table 1 Parameters of silicon-carbon composite materials
[0152]
[0153] Table 2 Preparation method parameters
[0154]
[0155] Performance Testing
[0156] Preparation of a lithium-ion battery for testing
[0157] Preparation of negative electrode sheet: 19.2wt% of the silicon-carbon composite material prepared in the embodiment and the comparative example, 76.8wt% of graphite, 1.5wt% of single-walled carbon nanotubes, 2wt% of polyacrylic acid and 0.5wt% of carboxymethyl cellulose are mixed evenly with water to obtain a negative electrode slurry with a solid content of 45%; the obtained negative electrode slurry is transferred to a coating machine, coated on the upper and lower surfaces of the copper foil, and then dried, compacted and cut in sequence to obtain a negative electrode sheet; wherein the thickness of the negative electrode active layer on each side is 45μm, and the surface density is 70mg / 10cm 2 ;
[0158] Preparation of positive electrode sheet: 96wt% positive electrode active material (commercial high nickel ternary, NCM811), 2.5wt% conductive carbon nanotubes, 1.5wt% polyvinylidene fluoride and N-methylpyrrolidone were mixed evenly and filtered with a 200-mesh filter; the obtained positive electrode slurry was transferred to a coating machine, coated on the upper and lower surfaces of aluminum foil, and then dried, compacted and cut in sequence to obtain a positive electrode sheet; wherein the thickness of the positive electrode active layer on each side is 43μm, and the surface density is 145mg / 10cm 2 ;
[0159] Diaphragm: Polypropylene film is used as the diaphragm with a thickness of 14 μm;
[0160] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (EDC) were mixed in a volume ratio of 1:1:1, and then 1 mol / L LiPF6 was added and mixed evenly to prepare an electrolyte;
[0161] The positive electrode sheet to be assembled, the separator, and the negative electrode sheet to be assembled are stacked in sequence, so that the separator is located between the positive electrode sheet and the negative electrode sheet to play an isolating role, thereby obtaining a bare battery cell; the bare battery cell is placed in a battery casing, and after drying, an electrolyte is injected, and vacuum packaging, standing, forming and shaping processes are sequentially performed to obtain a lithium-ion battery.
[0162] It should be noted that the above-mentioned test lithium-ion battery is only an example listed for testing the performance of the silicon-carbon composite material, and the present invention is not limited to this kind of battery, wherein the raw materials (except the silicon-carbon composite material), proportions, parameters and processes can be replaced with other conventional raw materials, proportions, parameters and processes in the art, thereby forming a battery different from the test lithium-ion battery.
[0163] 1. Dynamic performance (fast charging performance) test
[0164] Lithium deposition test: At 25°C, the lithium-ion batteries prepared in the examples and comparative examples were fully charged and discharged at a rate of 4C, with a charge cut-off voltage of 4.4V and a discharge cut-off voltage of 2.5V. After repeating 10 times, the negative electrode plates were disassembled and the lithium deposition on the surface of the negative electrode plates was observed. Among them, the area of lithium deposition on the surface of the negative electrode plates is less than 5%, which is considered to be slight lithium deposition; the area of lithium deposition on the surface of the negative electrode plates is 5%-40%, which is considered to be moderate lithium deposition; the area of lithium deposition on the surface of the negative electrode plates is greater than 40%, which is considered to be severe lithium deposition.
[0165] 2. First-effect test
[0166] At 25° C., the lithium ion batteries prepared in the examples and comparative examples were charged at a rate of 0.33C and discharged at a rate of 0.33C, with a charge cutoff voltage of 4.4 V and a discharge cutoff voltage of 2.5 V. A full charge and discharge cycle test was performed.
[0167] Wherein, first efficiency % = first discharge capacity / first charge capacity×100%.
[0168] 3. Normal temperature cycle performance test
[0169] At 25°C, the lithium ion batteries prepared in the examples and comparative examples were charged at a rate of 1C and discharged at a rate of 1C, with a charging cut-off voltage of 4.4V and a discharging cut-off voltage of 2.5V. Full charge and discharge cycle tests were performed until the capacity of the lithium ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0170] 4. High temperature cycle performance test
[0171] At 45°C, the lithium ion batteries prepared in the examples and comparative examples were charged at a rate of 1C and discharged at a rate of 1C, with a charging cut-off voltage of 4.4V and a discharging cut-off voltage of 2.5V. Full charge and discharge cycle tests were performed until the capacity of the lithium ion battery decayed to 80% of the initial capacity, and the number of cycles was recorded.
[0172] 5. Ultimate compaction test
[0173] At 25°C, the negative electrode sheets prepared in the examples and comparative examples were roller pressed to control the compaction density to be in the range of 1.50-1.75 g / cm 3 Observe the negative electrode sheet after rolling; if there are obvious overpressure marks on the surface of the negative electrode sheet, the compaction density at this time is determined to be the ultimate compaction density of the negative electrode sheet. It is reflected by the energy density under ultimate compaction.
[0174] The results of the above performance tests are shown in Table 3.
[0175] Table 3 Performance test results
[0176]
[0177]
[0178] It can be seen from the test results in the examples and comparative examples that the lithium-ion battery prepared by using the silicon-carbon composite material of the present invention has excellent energy density, kinetic performance and cycle performance.
[0179] From Table 3, we can see that:
[0180] In Comparative Example 1, since the particle size of the biomass carbon-based silicon-carbon material, the particle size of the resin carbon-based silicon-carbon material, and the particle size of the silicon-carbon composite material are all too small, the compaction density is significantly reduced; and the too small particle size increases the specific surface area and active sites of the obtained composite material, which may induce more side reactions, resulting in a decrease in the first efficiency of the battery cell and deterioration of the high-temperature performance.
[0181] In Comparative Examples 2 and 3, since the particle sizes of biomass carbon-based silicon-carbon materials, resin carbon-based silicon-carbon materials, and silicon-carbon composite materials are all too large, the ion transmission path is increased and they cannot be evenly dispersed among the graphite particles, which in turn leads to deterioration of the rate performance of the lithium-ion battery and severe lithium plating at the interface.
[0182] Comparative Example 4 Since the height-width ratio of the particles of the resin-based carbon-based silicon-carbon material in the silicon-carbon composite material is small, that is, the material has a high degree of flatness in morphology, it is easier to be crushed after rolling as a compressive component in the silicon-carbon composite material, so that more silicon material is exposed to the electrolyte, increasing more side reactions, and thus causing a significant deterioration in high-temperature performance. Although the high-temperature performance is improved as the sphericity increases, it is still far worse than the normal level, as shown in the results of Comparative Examples 5 and 6.
[0183] Comparative Example 7 Since the number of particles of the resin-based carbon-based silicon-carbon material in the silicon-carbon composite material is small, the particle size of the synthesized silicon-carbon composite material particles is too small, which leads to a significant decrease in its compaction ability. In addition, the small particle size of the silicon-carbon composite material particles will also lead to obvious side reactions and deterioration of high-temperature cycle performance.
[0184] Comparative Example 8 Since there are a large number of biomass carbon-based silicon-carbon materials and resin carbon-based silicon-carbon materials in each of the silicon-carbon composite particles, the particle size of the synthesized silicon-carbon composite particles is too large, the ion transmission path is increased, and the fast charging performance is deteriorated; and the resin carbon-based silicon-carbon material is the compressive component in the silicon-carbon composite material, and its number of particles is less than that of the biomass carbon-based silicon-carbon material, resulting in reduced compaction. As the number of biomass carbon-based silicon-carbon materials increases, it can be seen that the ultimate compaction of the silicon-carbon composite material decreases significantly, as shown in the results of Comparative Example 9.
[0185] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0186] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material comprises a mixed silicon-carbon material and a carbon coating layer coated on the surface of the mixed silicon-carbon material; The mixed silicon-carbon material includes a biomass-based carbon-based silicon-carbon material and a resin-based carbon-based silicon-carbon material; In the silicon-carbon composite material, by mass percentage, the content of the biomass carbon-based silicon-carbon material is 25-45wt%, the content of the resin carbon-based silicon-carbon material is 50-70wt%, and the content of the carbon coating layer does not exceed 5wt%.
2. The silicon-carbon composite material according to claim 1, characterized in that: The D50 particle size of the biomass carbon-based silicon-carbon material is 0.5-5 μm, preferably 1-3 μm; And / or, the pore size of the biomass-based carbon-based silicon-carbon material is 0.3-500 nm; And / or, in the biomass carbon-based silicon-carbon material, the carbon content is 50-70wt%, and the silicon content is 30-50wt%, calculated by mass percentage.
3. The silicon-carbon composite material according to claim 1 or 2, characterized in that: The D50 particle size of the resin-based carbon-based silicon-carbon material is 3-8 μm, preferably 3-5 μm; And / or, the resin-based carbon-based silicon-carbon material has mesopores and micropores; the pore size of the mesopores is 5-20 nm, and the pore size of the micropores is 0.1-2 nm; And / or, in the resin-based carbon-based silicon-carbon material, the carbon content is 50-70wt% and the silicon content is 30-50wt% by mass percentage; And / or, the aspect ratio γ of each particle of the resin-based carbon-based silicon-carbon material satisfies 0.6≤γ≤1, preferably 0.7≤γ<1.
4. The silicon-carbon composite material according to any one of claims 1 to 3, characterized in that: The D50 particle size of the silicon-carbon composite material is 10-25 μm, preferably 12-20 μm; and / or, in each silicon-carbon composite material particle, the number of particles of the biomass-based carbon-based silicon-carbon material is 1 to 3 on average; and / or, in each silicon-carbon composite material particle, the number of particles of the resinous carbon-based silicon-carbon material is 2-4 on average; And / or, the thickness d of the carbon coating layer satisfies 100 nm <d<200nm。 5. A method for preparing the silicon-carbon composite material according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: (1) first mixing a biomass-based carbon-based silicon-carbon material and a resin-based carbon-based silicon-carbon material to obtain a mixed dry material; (2) performing a second mixing of the mixed dry material obtained in step (1) and the coating agent, and then granulating and coating the mixed dry material to obtain a silicon-carbon composite material precursor; (3) Carbonizing the silicon-carbon composite material precursor obtained in step (2) to obtain a silicon-carbon composite material.
6. The preparation method according to claim 5, characterized in that: Step (1) The first mixing time is 10-30 min, preferably 15-25 min; And / or, the second mixing time in step (2) is 20-60 min, preferably 25-40 min; And / or, the coating agent in step (2) includes a solid phase coating agent or a liquid phase coating agent.
7. The preparation method according to claim 6, characterized in that: The solid phase coating agent includes one or more of asphalt, coal tar or petroleum tar, preferably coal tar and / or petroleum tar; And / or, the liquid coating agent is a resin solution; the resin in the resin solution includes phenolic resin and / or epoxy resin; the solvent in the resin solution includes one or more of ketone solvents, alcohol solvents, halogenated alkane solvents, ether solvents or ester solvents.
8. The preparation method according to any one of claims 5 to 7, characterized in that: The temperature of the carbonization treatment in step (3) is 300-800° C., preferably 400-600° C.; And / or, the heating rate of the carbonization treatment in step (3) is 2-10°C / min, preferably 5-8°C / min; And / or, the holding time of the carbonization treatment in step (3) is 100-200 min; And / or, the carbonization treatment in step (3) is carried out under a protective atmosphere.
9. A negative electrode plate for a lithium ion battery, characterized in that: It includes the silicon-carbon composite material as described in any one of claims 1 to 4, or the silicon-carbon composite material prepared by the preparation method as described in claims 5 to 8.
10. A lithium ion battery, characterized in that: Comprising the negative electrode plate of a lithium-ion battery as claimed in claim 9.
